Up-Regulated Expression of Plasminogen Activator Inhibitor-1 in Hep G2 Cells: Interrelationship between Insulin and Insulin-Like Growth Factor 1 - Anfosso, F; Alessi, M C; Nalbone, G; Chomiki, N; Henry, M; Juhan-Vague, I (Thrombosis and Haemostasis, 1995)
Insulin resistance represents a situation with a high risk of athero-thrombosis and is accompanied by increased plasma plasminogen activator inhibitor-1 (PAI-1) levels. Fasting insulin level is highly correlated with PAI-1 levels in plasma. It has been shown that insulin increases PAI-1 synthesis by the human hepatoma cell line Hep G2. Moreover when Hep G2 cells expressing a down-regulation of insulin receptors by incubation with 10-7 M insulin, were stimulated by 10-9 M insulin, an overexpression of PAI-1 synthesis was observed despite a reduced number of insulin receptors. Insulin-like growth factor 1 (IGF-1) shares many properties with insulin. The aim of the present study was to evaluate the effect of IGF-1 on PAI-1 synthesis by Hep G2 cells down-regulated either by insulin or IGF-1.Incubation of Hep G2 cells with increasing doses from 10-9 to 10-7 M IGF-1 induced a dose-dependent stimulation of PAI-1 synthesis up to 4.5-fold the control level. When cells were first pre-incubated with 10-7M IGF-1 for 18 h, acid washed, and then stimulated with 10-9 M IGF-1, the expression of IGF-1 receptors was greatly reduced (up to 70%). In contrast PAI-1 secretion was increased 3.4-fold the level of control cells and by 1.9-fold the level of cells first stimulated with 10-9M IGF-1. Both transcripts of PAI-1 mRNA were also increased. The overexpression of PAI-1 synthesis was observed irrespective of the hormone used in the down-regulation step (i.e. 10-9 M insulin or IGF-1) or in the stimulation step (i. e. 10-9 M insulin or IGF-1). The results showed an interrelationship between insulin and IGF-1 on PAI-1 synthesis in down-regulated Hep G2 cells. They also suggest that in the insulin resistant state, IGF-1 would be able to participate in the increase in PAI-1 plasma levels by stimulating down-regulated insulin target cells.